The Differences Of Matrix Metalloproteinase 9 and Tissue Inhibitor Matrix Metalloproteinase 1 Expression Between Nullipara and Postpartum on Vaginal Wall Of Rattus Norvegicus - Novida Ariani (Science Midwifery, 2021)
The pathophysiology of how the labor process changes the molecular and biochemical changes of the pelvic floor, especially the vaginal wall, causing the female pelvic organ prolapse is not clear. This change is presumed through the mediation of changes in Matrix Metalloproteinase 9 (MMP-9) and Tissue Inhibitor Matrix Metalloproteinase 1 (TIMP-1). Therefore, this study aims to determine changes in MMP-9 and TIMP-1 in postpartum. This research is an observational cohort study on female rats Rattus norvegicus Wistar strain. Replication used was 5 individuals for each nulliparous group, postpartum day-1, day-3 and day-7. Selection of mice by using random allocation. The vaginal wall tissue slides were stained with immunohistochemistry. MMP-9 and TIMP-1 expressions were calculated and analyzed using Analysis of Variance (ANOVA). The results of this study indicate that there is a significant difference (p = 0.007) mean expression of MMP-9 per visual field on the vaginal wall among nullipara (11.2 ± 1.304), postpartum day-1 (13.2 ± 2,387), day- 3 (12.6 ± 2.191), and day-7 (8.0 ± 2,550). There was an increasing trend of MMP-9 expression on the 1st day postpartum, then MMP-9 gradually decreased until postpartum on the 7th day. The results in this study also showed that there was a significant difference (p = 0.028) in the mean of TIMP-1 expression on the vaginal wall between nulliparous rats (11.6 ± 1.342), postpartum day -1 (15.4 ± 3.130), day -3 (13.2 ± 2.683), and day-7 (10.8 ± 1.483). There was increased expression of TIMP-1 day-1 postpartum than nullipara, then decreased gradually until the 7th day postpartum.